2009
DOI: 10.1074/jbc.m109.030247
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ATP-binding Cassette Protein AtMRP5/AtABCC5 Is a High Affinity Inositol Hexakisphosphate Transporter Involved in Guard Cell Signaling and Phytate Storage

Abstract: Arabidopsis possesses a superfamily of ATP-binding cassette (ABC) transporters. Among these, the multidrug resistance-associated protein AtMRP5/AtABCC5 regulates stomatal aperture and controls plasma membrane anion channels of guard cells. Remarkably, despite the prominent role of AtMRP5 in conferring partial drought insensitivity upon Arabidopsis, we know little of the biochemical function of AtMRP5. Our phylogenetic analysis showed that AtMRP5 is closely related to maize MRP4, mutation of which confers a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
201
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 46 publications
1
201
1
Order By: Relevance
“…Members of this family have also been shown to transport GSH conjugates and to confer cadmium resistance in plants and humans (23)(24)(25)(26). In addition, for many ABCC proteins in Arabidopsis, vacuolar localization has been demonstrated or proposed on the basis of data obtained using either Western blotting of membrane fractions, GFP fusion proteins, or vacuolar proteomics approaches (27)(28)(29)(30). We have therefore isolated homozygous knockout lines for all 15 Arabidopsis ABCC genes and have grown these mutants in the presence of arsenic and arseniccontaining herbicides.…”
Section: Resultsmentioning
confidence: 99%
“…Members of this family have also been shown to transport GSH conjugates and to confer cadmium resistance in plants and humans (23)(24)(25)(26). In addition, for many ABCC proteins in Arabidopsis, vacuolar localization has been demonstrated or proposed on the basis of data obtained using either Western blotting of membrane fractions, GFP fusion proteins, or vacuolar proteomics approaches (27)(28)(29)(30). We have therefore isolated homozygous knockout lines for all 15 Arabidopsis ABCC genes and have grown these mutants in the presence of arsenic and arseniccontaining herbicides.…”
Section: Resultsmentioning
confidence: 99%
“…However, AtABCC2 was previously shown to exhibit a higher transport activity for several substrates compared with AtABCC1 when expressed in the same pYES3 vector (Lu et al, 1998). To validate that MgATPactivated uptake of ABA-GE into yeast vesicles expressing AtABCC2 has the characteristics of ABC transportermediated transport, we tested the effects of the ABC transporter inhibitors orthovanadate and probenecid (Nagy et al, 2009) on AtABCC2-expressing yeast vesicles. The presence of 1 mM orthovanadate and 1 mM probenecid strongly inhibited the MgATP-enhanced ABA-GE uptake by 92% and 90%, respectively, which corresponds to the uptake activity in the absence of MgATP (Table II).…”
Section: Kinetics Of Vacuolar Aba-ge Importmentioning
confidence: 99%
“…In patch-clamp experiments, it was found that mrp5 mutant guard cells displayed reduced ABA activation of plasma membrane Ca 2+ and S-type anion currents as well as reduced activation of anion currents by cytoplasmic Ca 2+ (Suh et al, 2007). While it was initially thought that the transporter localizes to the plasma membrane, it was later reasoned that it is vacuole localized (Nagy et al, 2009). To explain the observed mutant phenotypes, the authors hypothesized that excess cytosolic IP 6 in the mrp5 mutant might complex cytosolic Ca 2+ or increase its release from the vacuole through the stimulation of putative IP 6 -sensitive vacuolar Ca 2+ channels.…”
Section: Other Vacuolar Transport During Stomatal Movementmentioning
confidence: 99%
“…It is a guard cell-expressed ABC-type transporter that mediates high-affinity uptake of IP 6 into vacuoles (Nagy et al, 2009). Although AtMRP5/AtABCC5 also is expressed in other cell types, mrp5 knockout mutant plants show strong guard cell mutant phenotypes (Klein et al, 2003).…”
Section: Other Vacuolar Transport During Stomatal Movementmentioning
confidence: 99%
See 1 more Smart Citation